Indicators and criteria for assessing achievement of renewable energy utilization in communities - Tantranont, Nuttiya; Yaowarat, Phatcharin; Pattarapremcharoen, Mechai; Thanarak, Prapita (Journal of Renewable Energy and Smart Grid Technology, 2018)
This research has objectives to develop indicators and criteria for assessing achievement in using renewable energy for communities. The researchers used Delphi technique for interviewing to collect opinions from experts who had strong experience in renewable energy utilization in the Northern region of Thailand. The 8 indicators for achieving assessment on community renewable energy utilization consisted of perception, attitude/motivation, learning, community potential, leaders, community and household participation, problem solving, and internal and external networks. The criteria for achievement assessment consisted of 4 levels of scores that range from 0 – 100 points. The 4 levels are Excellent, Good, Fair, and Poor, according to potential of the community. For success in supporting the use of renewable energy in communities, participation and cooperation from people in the community and external organizations are essential. These sectors need to get involved and play important roles to push forward and maintain sustainable production and utilization of renewable energy in communities.